Effect of Bloodletting Therapy on Patients with Spastic Wrist Dorsiflexion Dysfunction after Stroke - LIN Wanqing; XIE Xuemin; CHEN Bin; ZHENG Xinyi (康复学报)
ObjectiveTo observe the effect of bloodletting therapy on limb spasticity, wrist dorsiflexion function, surface electromyography, upper limb motor function of patients with spastic wrist dorsiflexion dysfunction after stroke.MethodsA total of 70 patients with spastic wrist dorsiflexion dysfunction after stroke in the People's Hospital Affiliated to Fujian University of Traditional Chinese Medicine were randomly divided into the control group and the experimental group according to the random sequence was generated by SPSS 22.0 software, with 35 cases in each group. The control group received routine medical treatment, rehabilitation treatment and acupuncture therapy. Yangxi (LI 5), Yangchi (TE 4), Daling (PC 7) acupoint of the affected hand were selected for acupuncture treatment, Yangxi (LI 5) acupoint was straightly needled 0.5-0.8 inch, Yangchi (TE 4) and Daling (PC 7) acupoints were straightly needled 0.3-0.5 inch, 30 minutes each time, once a day, five times a week, continous treatment for four weeks. The experimental group was given bloodletting therapy on the basis of routine medical treatment and rehabilitation treatment in the control group. The operation acupoints of bloodletting therapy were the same as those of the control group, once every other day, three times a week, continous treatment for four weeks. Before treatment and after treatment for four weeks, the modified Ashworth scale (MAS) was used to evaluate limb spasticity; passive range of motion (PROM) of wrist dorsiflexion joint was used to evaluate wrist dorsiflexion function; the simplified Fugl-Meyer assessment upper extremity scale (FMA-UE) was used to evaluate upper limb motor function; surface electromyography such as integrated electromyogram (iEMG) and root-mean-square value (RMS) were used to evaluate the functional status of the neuromuscular system on the affected side; the clinical effects of the two groups were compared.ResultsThere was no significant difference in MAS grade, PROM score, iEMG, RMS, and FMA-UE score between the two groups before treatment (P>0.05). Compared with before treatment, the MAS grade, iEMG and RMS of the two groups were significantly decreased after treatment, and the PROM score, FMA-UE score were significantly increased (P<0.05). Compared with the control group, the MAS grade, iEMG and RMS of the experimental group were significantly lower, and the PROM score, FMA-UE score were significantly higher (P<0.05). There was no significant difference in the total effective rate between two groups (P>0.05), while the obvious effective rate of the experimental group was significantly higher than the control group (P<0.05).ConclusionBloodletting therapy can improve the spasticity of wrist flexor muscle in patients with spastic wrist dorsiflexion dysfunction after stroke, reduce the abnormal muscle contraction, and improve the passive range of motion of wrist joint and limb motor function. It is worthy of clinical application and promotion.